Domestic Terrorism, Religious Insurgency, and the National Security Question in Nigeria - Ugwuoke, Cyril O.; Ugwuanyi, Lois Chidera; Ngwu, Elias C. (University of Nigeria Journal of Political Economy, 2022)
The paper reports the findings of a study on domestic terrorism and religious insurgency in Nigeria. It focused on the impacts of the religious insurgency and the ongoing war on terrorism. It applied accidental sampling technique due to the tension and insecurity atmosphere in the study area the Northeast of Nigeria, and used other administered questionnaire to sample 250 respondents who were in a mood to respond to investigation. The findings indicate that the activities of Boko Haram terrorist group are strong enough to stretch the ability of the Nigeria military and equally threaten the sovereignty of the state. It further found that the current strategies adopted by the Nigerian government to combat terrorism have reduced the fighting powers of the terrorism but the war is still ongoing, taking both military and civilian causalities and many refugees are still in camps. The paper recommends the importance of inter-religious committees, redressing palpable social inequality and to open communication to dialogue with the terrorists.